Study the Effect of Ethical Principles on Job Commitment and Employees' Satisfaction - Pourmofrad, Ahmad Reza; Mohammadian, Moghaddaseh (International Review of Management and Marketing, 2017)
This study is conducted with the aim of investigating the effect of ethical principles on job commitment and employees' satisfaction among employees of industry and trade organization of Fars province in 2016. The research method is inferential, descriptive, survey and cross-sectional. To measure the research variables, the questionnaire in the form of 5-item Likert is used. To analyze the data, descriptive statistics (investigating the status of frequency on the basis of gender, age, education in the statistical sample, how the distribution of research) and inferential analysis of findings (Kolmogorov-Smirnov tests of index of normality of distribution, KMO as an indicator of the adequacy of the sampling, and the results of Pearson correlation) is used. Hypotheses testing showed that there is a relationship between the dimension of ethic and satisfaction and between the dimension of ethic and commitment. Keywords: Ethical Principles, Job Commitment, Employees' Satisfaction JEL Classification: J28